(untitled) (Asian Journal of Social Science Studies, 2022)
In order to better answer these questions, this thesis will be divided into four chapters. Chapter 1 “Theorising the Kaifeng Jewish descendants” reviews three bodies of literature: (a) Jews and China—a historical encounter, (b) conceptualising emerging Jewish communities, and (c) disputed Jewishness in Israel‟s immigration policy, so that to situate the Kaifeng Jewry issue in a broader societal and academic discourse. Chapter 2 “Kaifeng Jewry in the PRC” traces the development of the community from the 1950s to the 1990s, revolving around the ethnic classification campaign that erased Kaifeng Jewry from China‟s minzu picture and the modification campaign in 1996 that erased Jewish minzu on paper officially. Chapter 3 “To “return” or to stay, that is the question” invokes accounts of four Kaifeng Jewish descendants who made different choices regarding aliyah and concludes with their motivation either to “return” or to stay. Chapter 4 “Being Chinese in the promised land” investigates the Kaifeng immigrants‟ mixed identity as being Chinese and Jewish simultaneously, proposing an examination of “Israeliness” as a competing, alternative socio-cultural awareness to “Chineseness;” it also looks into the racialisation logic and racism confronted by the Kaifeng immigrants that contain their integration into Israeli society.